2020
DOI: 10.1161/circinterventions.120.009155
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic Value of Quantitative Flow Ratio Based Functional SYNTAX Score in Patients With Left Main or Multivessel Coronary Artery Disease

Abstract: Background: The potential impact of quantitative flow ratio (QFR) based functional Synergy Between Percutaneous Coronary Intervention With Taxus and Cardiac Surgery (SYNTAX) score (FSS QFR ) on prognostication and revascularization strategy choice has not been fully investigated, and the discriminant ability of FSS QFR needs further validation. Methods: QF… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
25
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 26 publications
(26 citation statements)
references
References 25 publications
1
25
0
Order By: Relevance
“…Several studies have validated the accuracy and high correlation of QFR with FFR as a diagnostic reference [44][45][46]. Furthermore, QFR incorporation into functional SYNTAX score improves the prognostication and revascularization strategy choice compared to anatomic assessment alone in patients with left main or multivessel coronary artery disease [47]. QFR computation may also be a reliable tool to guide revascularization of non-infarct coronary arteries in the acute setting for patients with STEMI [48,49].…”
Section: Future Directionsmentioning
confidence: 99%
“…Several studies have validated the accuracy and high correlation of QFR with FFR as a diagnostic reference [44][45][46]. Furthermore, QFR incorporation into functional SYNTAX score improves the prognostication and revascularization strategy choice compared to anatomic assessment alone in patients with left main or multivessel coronary artery disease [47]. QFR computation may also be a reliable tool to guide revascularization of non-infarct coronary arteries in the acute setting for patients with STEMI [48,49].…”
Section: Future Directionsmentioning
confidence: 99%
“…Coronary angiography was performed using standard techniques. 11 Angiographic views were obtained after administration of intracoronary nitrate (100 or 200 mg). All angiograms were analyzed at a core laboratory (CCRF, Beijing, China) in a blinded fashion.…”
Section: Angiographic Analysis and Quantitative Coronary Angiographymentioning
confidence: 99%
“…QFR measurements were conducted for all eligible patients in PANDA III trial as described before. 11,12 In brief, vessels with lesions of ≥ 50% diameter stenosis and reference luminal diameter ≥ 2.5 mm by visual assessment were identified as vessels in need of QFR measurement. Off-line QFR analysis was performed blindly by well-trained analysts from an independent core laboratory (CCRF, Beijing, China), using QFR system (AngioPlus, Pulse Medical Imaging Technology, Shanghai, China).…”
Section: Measurements Of Quantitative Flow Reservementioning
confidence: 99%
“…The FSS QFR can potentially further refine prognostic risk estimation when compared with the classic anatomic SYNTAX score. Additionally, Zhang et al 40) reported that the FSS QFR in patients with left main or multivessel coronary disease was an independent predictor of the 2-year MACE.…”
Section: Risk Stratification In Multivessel Diseasementioning
confidence: 99%